Pengaruh Media Wayang terhadap Kemampuan Bahasa Lisan pada Anak Usia 5-6 Tahun di TK Islam Al-Anshor Palembang - Lucia Septiana Utami; Febriyanti Febriyanti; Kurnia Dewi; Mardiah Astuti; Indah Dwi Sartika (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to determine the effect of puppet media on oral language skills in children aged 5-6 years at Al-Anshor Islamic Kindergarten Palembang. This research method is the Experimental Method. This experimental method is a method that seeks influence on something between cause and effect carried out by researchers. This researcher uses the Pre Experimental Design type with One Group Pretest-Posttest Designs. The population of this study was 13 children in group B at Al-Anshor Islamic Kindergarten Palembang. The observations that researchers use with the determination to determine the influence of group B children aged 5-6 years at Al-Anshor Islamic Kindergarten Palembang. Based on the results of the research and discussion that has been carried out, there has been an increase in oral language skills in children. It can be said that in this study there is a significant influence given puppet activities, this is shown in the post-test experiment using story books. Before the puppet activities were implemented, children who had low fine motor development abilities were 3 children, while those with moderate scores were 10 children. After the wayang activity was implemented, 6 children had a high score or developed very well in their language skills, while 4 children had motor development skills that developed according to expectations, and only 3 children had a starting to develop score, which means that after being given treatment, children's fine motor development increased compared to before the treatment, and the Wayang activity was to improve the language skills of early childhood.